Improving opportunities for SMEs in Bangladesh-challenges and prospect identified with a eeference to BRAC Bank services - Biswas, Pollobe (BRAC University, 2018)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Masters of Business Administration, 2017.